Effects of C282Y, H63D, and S65C HFE gene mutations, diet, and life-style factors on iron status in a general Mediterranean population from Tarragona, Spain - Aranda, Núria; Viteri, Fernando E; Montserrat, Carme; Arija, Victoria (Annals of hematology, 2010)
Mutations in the HFE gene result in iron overload and can produce hereditary hemochromatosis (HH), a disorder of iron metabolism characterized by increased intestinal iron absorption. Dietary quality, alcoholism and other life-style factors can increase the risk of iron overload, especially among genetically at risk populations. Polymorphisms of the HFE gene (C282Y, H63D and S65C) were measured together with serum ferritin (SF), transferrin saturation (TS) and hemoglobin, to measure iron status, in randomly-selected healthy subjects living in the Spanish Mediterranean coast (n = 815; 425 females, 390 males), 18 to 75 years of age. The intake of dietary components that affect iron absorption was calculated from 3-day dietary records. The presence of C282Y/H63D compound heterozygote that had a prevalence of 2.8% in males and 1.2% in females was associated with an elevated TS and SF. No subject was homozygous for C282Y or S65C. The C282Y heterozygote, H63D heterozygote and homozygote and H63D/S65C compound heterozygote genotypes were associated with increased TS relative to the wild type in the general population. These genotypes together with the alcohol and iron intake increase the indicators of iron status, while calcium intake decreases them. We did not observe any affect of the S65C heterozygote genotype on these levels. All the HFE genotypes except for the S65C heterozygote together with the alcohol, iron and calcium intake affect the indicators of iron status. The C282Y/H63D compound heterozygote genotype has the higher phenotypic expression in our Spanish Mediterranean population.